Analisis Perbedaan Empati Anak Usia Dini Ditinjau Berdasarkan Jenis Kelamin di TK X di Kecamatan Purwakarta - Aprilliani, Karisya; Maranatha, Jojor Renta; Justicia, Risty (AS-SABIQUN, 2023)
This research was conducted with the aim of analyzing differences in early childhood empathy in terms of gender in Purwakarta District. The participants in this study were early childhood with the criteria of 5-6 years in Kindergarten in Purwakarta Subdistrict, consisting of 7 girls and 7 boys. This study used a qualitative research method with a descriptive approach. Data collection techniques in this study used observation and documentation. The data that has been collected is then analyzed using the Milles and Huberman data analysis model. The results showed that there were differences in empathy for early childhood in terms of gender in Purwakarta District where girls have higher empathy than boys or girls have better empathy than boys.